Correlation Between C–H∙∙∙Br and N–H∙∙∙Br Hydrogen Bond Formation in Perovskite CH3NH3PbBr3: A Study Based on Statistical Analysis - Alejandro Garrote-Márquez; Norge Cruz Hernández; Eduardo Menéndez-Proupin (Solids)
This study investigates the potential correlation between C—H···Br and N—H···Br hydrogen bonds in CH3NH3PbBr3 over a broad temperature range (50–350 K), using a statistical analysis of molecular dynamics simulations. The analysis focused on quantifying the relationship between both hydrogen bond types via Pearson and Spearman correlation coefficients, derived from extensive datasets obtained from simulation trajectories. The results revealed a notable discrepancy between the two coefficients at low temperatures (T ≤ 125 K): While Spearman’s values suggested a strong monotonic correlation, Pearson’s values indicated a lack of linear association. Further analysis through data segmentation and block averaging demonstrated that the high Spearman coefficients at low temperatures were not statistically robust. At higher temperatures (T > 125 K), both correlation coefficients consistently exhibited low values, confirming the absence of meaningful correlation. These findings suggest that the formation of C–H···Br and N–H···Br hydrogen bonds occurs independently, with no evidence of cooperative behavior.